Influnce of Dietary Soy Acid Oil on Growth Performance, Carcass Characteristics and Chemical Composition of Muscles in Broiler Chicken - Dubey, Meenu; Tiwari, S.P.; Tiwari, R.P.; Khune, V.N.; Doneria, Raina (Indian Journal of Animal Nutrition, 2018)
Day old Vencobb broiler chicks (n= 360) were randomly divided into 6 treatment groups with 4 replicates of 15 chicks in each. Group T1 served as control while treatments T2, T3, T4, T5 and T6 contained 1, 1.5, 2, 2.5 and 3% of soy acid oil (SAO) in the diet, respectively. The body weight at 6 week of age was higher (P